Alternative Piping Material For Malaysian Fuel Gas Distribution - Abdul Majid, Zulkifli; Yaacob, Zulkefli (Penerbit UTM Press, 2001)
Fuel gas distribution system in Malaysia can be divided into the Natural Gas (NG) and the Liquefied Petroleum Gas (LPG) distribution system. The distribution pipeline system for NG and LPG in Malaysia are using either steel pipes or plastic pipes (polyethylene pipe). However it has become common in other parts of the world such as the United States, Australia, Canada, Europe and Japan that copper pipes are being used for their distribution system. They have found that copper is an alternative for safe and superior piping material suitable for interior distribution systems. Therefore copper pipes should also be considered as an alternative piping material for Malaysian gas distribution.